FIELD DEVELOPMENT SCENARIO OF MARGINAL FIELD USING OPERATIONAL COOPERATION CONTRACT SYSTEM BASED ON ECONOMIC ANALYSIS - I Gede Devon Gautama (Jurnal Eksakta Kebumian, 2021)
Abstract— Pertamina EP currently manages many old fields and dozen of them are marginal fields that require serious handling to be able to increase the production of Pertamina EP. Operational Cooperation (KSO) is a cooperation contract between Pertamina EP that works with the contractor in the management of oil and gas field. The contractor works on a certain work area from Pertamina EP's marginal field, while the KKKS right remain in hands of Pertamina EP. The KSO offer an effort to optimize the marginal fields so that it is expected to increase the production of Pertamina EP. Pertamina EP is also expected to focus more on efforts to increase production in the main fields and other fields which begin to show sufficient production. This paper aims to analyze whether the “X” field has good economic or not. “X” field is analyzed based on the Operational Cooperation contract, then the NPV, POT, IRR and sensitivity analysis of oil price, investment, operating cost, production are obtained. The result of economic calculation and production forecasting are based on “X” field’s data obtained from “Y” company.Keywords—Marginal Field. Old Field, Operational Cooperation, Economic Analysis